Measuring the maturity of Information Technology Governance based on COBIT - Heba FASIHUDDIN; Somayah ALHARBI; Alanoud ALSHEHRI; Azzah ALZAHRANI; Hanin FATANI (Revista Română de Informatică și Automatică, 2022)
Information Technology (IT) is critical to strengthening corporate governance. Thus, organizations require a well-designed and implemented IT governance framework. This paper aims to evaluate the maturity level of IT governance in Saudi Arabia, via the COBIT IT governance framework. Three processes were investigated: defining a strategic IT plan; assessing and managing IT risks; and project management. A questionnaire was developed, based on the COBIT maturity model, and distributed among IT workers at different levels. Results demonstrate that the private sector is the most mature within the investigated areas; more development is required for the government sector and even the semi-government sector. The paper explores different points of strength and weakness in terms of IT governance maturity in different sectors. Moreover, it presents steps that may improve the IT governance maturity level in government and semi-government sectors. This could lead to more future research and investigation in different variables that may affect the development and maturity of IT governance.